Food packaging films from natural polysaccharides and protein hydrogels: A comprehensive review - Mou Zhao; Ping Han; Hongyan Mu; Suling Sun; Juan Dong; Jingtao Sun; Shiling Lu; Qingling Wang; Hua Ji (Food Chemistry: X)
The development of innovative, biodegradable food packaging materials to combat plastic pollution has garnered significant attention from scholars and government agencies worldwide. Natural polysaccharides and proteins exhibit excellent modifiability, biodegradability, high ductility, and compatibility with food products, making them ideal candidates for constructing hydrogels. Hydrogel films based on these biopolymers have opened new research horizons in food packaging applications. This review examines natural polysaccharides and proteins commonly used in hydrogel film preparation and explores strategies to improve their packaging performance, including the use of binary mixtures and exogenous additives. To optimize functionality, the cross-linking mechanisms between materials and film-forming methods are summarized. Additionally, recent applications of hydrogel films in food packaging in are discussed, showcasing their ability to extend or monitor food freshness. Despite existing challenges, the current advancements present a promising and sustainable alternative to conventional plastic materials paving the way for innovative packaging solutions.